Cloud-based cross-platform collaborative augmented reality in flutter - Carius, Lars; Eichhorn, Christian; Rudolph, Linda; Plecher, David A.; Klinker, Gudrun (Frontiers in Virtual Reality, 2022)
Augmented Reality (AR) has progressed tremendously over the past years, enabling the creation of collaborative experiences and real-time environment tracking on smartphones. The strong tendency towards game engine-based approaches, however, has made it difficult for many businesses to utilize the potential of this technology. We present a novel collaborative AR framework aimed at lowering the entry barriers and operating expenses of AR applications. Our framework includes a cross-platform and cloud-based Flutter plugin combined with a web-based content management system allowing non-technical staff to take over operational tasks such as providing 3D models or moderating community annotations. To provide a state-of-the-art feature set, the AR Flutter plugin builds upon ARCore on Android and ARKit on iOS and unifies the two frameworks using an abstraction layer written in Dart. We show that the cross-platform AR Flutter plugin performs on the same level as native AR frameworks in terms of both application-level metrics like CPU and RAM consumption and tracking-level qualities such as keyframes per second used by the SLAM algorithm, detected feature points, and area of tracked planes. Our contribution closes a gap in today’s technological landscape by providing an AR framework seamlessly integrating with the familiar development process of cross-platform apps. Using the AR Flutter plugin and the accompanying content management system, AR can be used as a tool to achieve business objectives and is not restrained to stand-alone single-purpose apps anymore, triggering a potential paradigm shift for previously complex-to-realize applications of AR, e.g. in production and planning. The AR Flutter plugin is fully open-source, the code can be found at: https://github.com/CariusLars/ar_flutter_plugin.